Wind turbine emulator based on blade element momentum theory for variable_speed wind power generation system - Sirichai Tammaruckwattana; Kazuhiro Ohyama; Shinji Arinaga (My University, 2015)
This paper proposes a wind turbine emulator (WTE) based on the blade momentum theory, and tests the variable‐speed wind power generation system using a pulse‐width modulation (PWM) converter to verify the accuracy of the emulator. The behavior of the wind turbine for natural wind is reproduced by the WTE based on the proposed theory. The variable‐speed wind power generation system employs a vector control system to control the torque and speed of the permanent magnet synchronous generator in the converter side. The windmill rotational speed is controlled to maximize the efficiency of the wind turbine against wind velocity. And the active power and reactive power are controlled in the inverter side, and the generated power is sent to the grid while controlling the DC link voltage to be constant at the same time. The behaviors of the WTE are compared with the simulation results and experimental results using a real wind turbine. These experimental and simulation results show that the test bench with the proposed WTE has sufficient performance and accuracy to verify variable‐speed wind generator systems. © 2015 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.
Keywords: Power optimizer; Windmill; Tip-speed ratio; Wind Turbine Control Systems